Nilai-Nilai Pendidikan Akhlak dalam Surat Al-Ahzab Ayat 35: (Studi Kasus di MA Mansyaul Ulum Ganjaran Gondang Legi) - Fina Nailil Rifqih; Luqman Hakim (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the moral education values contained in Surah Al-Ahzab verse 35 and their implementation at MA Mansyaul Ulum Ganjaran Gondanglegi. The research focuses on the values of faith, honesty, obedience, and patience, which are relevant for shaping students’ character. The method used is a case study with a descriptive qualitative approach. Data collection techniques were carried out through observation and interviews with students and teachers. The results of the study show that the value of faith is instilled through religious habituation activities at school, honesty is built by encouraging an anti-cheating attitude and responsibility, obedience is implemented through compliance with school rules and respect for teachers, while patience is trained through various learning activities that require perseverance. Although there are still students who have not fully applied good morals, the school's gradual efforts have shown positive results. This research emphasizes that the consistent application of moral values can help build students' character to become faithful, honest, obedient, and patient individuals who will benefit their future lives.